Pengaruh Strategi Pembelajaran Berdiferensiasi terhadap Literasi Sains Siswa Kelas V Sekolah Dasar Parigi Utara - Roslina Roslina; Jamaludin M Sakung; Unggul Wahyono; Afadil Afadil; Paulus Hengky Abram (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The purpose of this study was to determine the effect of learning strategies differentiated learning strategy against l iteration science on natural events material for fifth grade elementary school students in North Parigi sub-district with a total of 56 students. The samples of this study were the fifth grade class of SD Inpres 1 Toboli as the experimental class and SDN Inti P angi as the control class with the same number of students, namely 28 people. This research method uses true experimental research with the research design pretest-posttest nonequivalent control group design , data collection is done by means of observation and science literacy outcome test. Sampling was conducted using the p technique. urposive sampling technique Data analysis used SPSS 23 with the stages of normality test, homogeneity test and T test ( paired T sample). The research results at the time of pretest The average value of science literacy for the control class was 58.78, and the experimental class had an average value of 60.17. The average value of the post-test was 86.13 for the control class and 87.08 for the experimental class. Results output SPSS obtained a significance value smaller than the significance level of 0.05 (0.000 < 0.005) then H 0 is rejected and H 1 is accepted, so it can be concluded that there is an effect of differentiated learning strategies on science literacy on the material on science literacy in the material events nature in grade V elementary schools in the North Parigi sub-district.